2017
DOI: 10.1002/app.45477
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and poly(ionic liquid) modified polyurethane sponges with enhanced flame‐retardant properties

Abstract: Graphene (Gr) and poly(ionic liquid) (PIL) modified polyurethane (PU) sponges with enhanced flame‐retardant properties were prepared by the direct dip coating of Gr and ionic liquid (IL) monomers onto a PU sponge followed by the polymerization of IL monomers under thermal initiation. With a content of 1.5% Gr in IL, the limiting oxygen index (LOI) of PU–PIL–Gr was 26.1%, whereas the neat PU sponge showed an LOI of only 17.9%. The horizontal flame test results indicate that PIL–Gr prevented horizontal flame spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The oxygen index value increased from 21.3% to 25.2% because of N-Cl synergistic flame retardant effect. What's more, pure PU is highly combustible and its LOI value is only 16.7% according to the literature [26][27][28]. It can be concluded that the flame retardancy of IWPU was improved greatly compared with pure PU.…”
Section: Loi Testsmentioning
confidence: 95%
“…The oxygen index value increased from 21.3% to 25.2% because of N-Cl synergistic flame retardant effect. What's more, pure PU is highly combustible and its LOI value is only 16.7% according to the literature [26][27][28]. It can be concluded that the flame retardancy of IWPU was improved greatly compared with pure PU.…”
Section: Loi Testsmentioning
confidence: 95%
“…Based on these two reasons, the sample is beneficial for suppressing the progress of the combustion reaction and achieving an excellent flame‐retardant effect. In addition, the formation of an intumescent char layer provides a strong protective barrier (condensed‐phase flame retardancy) that arrests the contact of oxygen and the heat transfer, thereby preventing further burning of the substrate material …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the formation of an intumescent char layer provides a strong protective barrier (condensed-phase flame retardancy) that arrests the contact of oxygen and the heat transfer, thereby preventing further burning of the substrate material. [42][43][44] FTIR analysis was also conducted to confirm the structure of the residue chars for carbonized ACPM-1 obtained from the torch burn test, and the results are shown in Figure 11. For ACPM-1, comparing the spectra of the sample before and after the combustion, we found that the characteristic peaks remain basically unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…With the introduction of the concept of green chemistry, an upsurge in ILs research has gradually formed around the world. There are three main types of ILs used for flame retardant: use alone, 27,28 compound with traditional flame retardants, 29 and modify flame retardant and combine with traditional flame retardant 30,31 . When the ILs are used alone or combined with traditional flame retardants, the flame retardancy of the polymer is not ideal, while it modifying flame retardant and combining with traditional flame retardant is of great effect.…”
Section: Introductionmentioning
confidence: 99%